ANALISIS BIAYA PRODUKSI PADA CV. PURWA DAYA SEJAHTERA PALEMBANG - Titi Suelmi (Universitas Tridinanti, 2021)
The selling price of goods on an order basis is determined before production is carried out, the company will calculate the cost elements contained in the production in an estimate. This estimation is based on the standard cost that has been determined in advance by the company. If the economic conditions are assumed to be stable where prices are generally relatively constant, the estimated cost of production can approach the actual cost of production.In addition to the determination of the cost of goods manufactured above, the determination of the cost of goods manufactured using this order requires a separate form known as a job cost sheet. With the implementation of the cost price card, the cost of each order can be clearly identified.Keywords: Production costs, raw materials, labor costs, overhead costs